Advanced network programming - principles and techniques : network application programming with Java - Ciubotaru, Bogdan (London, United Kingdom : Springer, 2013)
This book coves in detail network architectures, including the latest wireless heterogeneous networks, communication protocol models, and protocols and support for communication-based services.
Chapter1. Introduction -- Chapter2. Network Architectures -- Chapter3. Network Communications Protocols and Services -- Chapter4. Basic Network Programming -- Chapter5. Sockets -- Chapter6. Socket-Based Client-Server Communication -- Chapter7. Support for Communication-Based Services -- Chapter8. Server-Side Network Programming -- Chapter9. Client-Side Network Programming -- Chapter10. Advanced Client-Server Network Programming -- Chapter11. Conclusion .
Includes index.
Keywords: INFORMATION TECHNOLOGY